RESERVES FOR INCREASING THE EFFICIENCY OF MANAGING SUBJECTS OF MARKET RELATIONS - Muha, Yu. O.; Yakovenko, V. V. (Science and Transport Progress, 2007)
The modern market relationship are being developed in Ukraine. It is necessary to employ the modern technologies in production and sails to enter competitive world markets successfully. There are two major ways to speed up turnover of investment: to shorten supply chain and to optimize production stock.